-15+X+6-10=-5

Simple and best practice solution for -15+X+6-10=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15+X+6-10=-5 equation:


Simplifying
-15 + X + 6 + -10 = -5

Reorder the terms:
-15 + 6 + -10 + X = -5

Combine like terms: -15 + 6 = -9
-9 + -10 + X = -5

Combine like terms: -9 + -10 = -19
-19 + X = -5

Solving
-19 + X = -5

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + X = -5 + 19

Combine like terms: -19 + 19 = 0
0 + X = -5 + 19
X = -5 + 19

Combine like terms: -5 + 19 = 14
X = 14

Simplifying
X = 14

See similar equations:

| 3x^2-4x=2x^2+4x-6 | | -3x-5=2x+7 | | 2(-5+4x)=86 | | W=p+2l | | [3y+1]-1=[y+4] | | 24-5p=17-4p | | 1/2x+y=-2 | | 2/21=-5/7w | | 18x+6= | | X^5+7x^3-18x=0 | | 5z^4+10z^2=54-11z^2 | | 2(4x-1)=5x+6 | | 7x-30=10+2x | | y=x^3-15x^2-600x+1000 | | 2*69+4= | | 1/4(5x-2)=8 | | -18/k=-6 | | 9(4b-1)=2(9b-3) | | 45-6C+65=9 | | -y=-54 | | -9=45 | | 40+14j=2(-7-20) | | 12x+14y+12+10x-6y-18= | | -9+x=-2x+0 | | 5x2/6 | | -8x-10=4x-14 | | (5p+10)/(2p+6)+(3p-15)/(2p+6) | | 2y+3x=4y+9x+7 | | -7x+7+9x=5x-15x | | 180(2x+4)=180 | | 2(5+-3v)+9v=28 | | 9/25x=6/5+3/5 |

Equations solver categories